PENINGKATAN KEAKTIFAN DAN PRESTASI BELAJAR MATEMATIKA MELALUI GOOGLE MEET BERBANTUAN JAMBOARD DAN PENTABLET - Zubaidah, Ida (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2022)
This Best Practice is motivated by the lack of activeness and learning achievements of students in online learning activities during the COVID-19 pandemic. This study is focused on efforts to enhance students' activeness and learning achievement in mathematics through Google Meet assisted by jamboard and pentablet applications. The subjects of this study were students of class VIII D of SMP Negeri 41 Semarang with a total of 32 people. Based on an analysis of the observations results during the study, student learning achievement shows an improvement, as evidenced by an increase in student activity scores compared to the results before using Google Meet assisted by Jamboard and Pentablet applications. Students learning activeness increased to 81.250%. In addition, the achievement of the minimum criteria of mastery learning percentage has increased, before this study by 56.25%, increasing to 84.375%. It can be concluded that online learning through Google Meet assisted by Jamboard and Pentablet applications can enhance student activeness and learning achievement.